Role of football scouts in player transformation process: From talented to elite athlete - Lazarević Snežana; Lukić Jelena; Mirković Vladimir (College of Sports and Health, Belgrade, 2020)
Revenues generated by football clubs belonging to one of the socalled "The Big Five" leagues (England, Germany, Spain, Italy and France) give a strong argument by claiming that modern football has become a very organized, but also profitable business. In the football clubs of the mentioned European countries, the most famous players of today are "super heroes" and they are the reason why massive numbers of football fans visit football stadiums. All players, who today identify themselves as elite athletes, were at the beginning of their sports careers merely talented individuals with more or less pronounced psycho-physical predispositions for playing sports. This paper will present the basic characteristics of the profession of professional scouts as one of the key persons in recognizing talents and their transformation into top athletes. Also, the paper emphasizes the necessary skills that these sports experts should possess, but also points out the importance of decisionmaking in terms of often difficult and complicated decisions in the process of identifying talented individuals in sports.